TRADISI MANDI MAYANG MASYARAKAT BANJAR KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Zainal Hakim; Achmad Hidir (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The Mandi Mayang tradition of the Banjar community in Keritang Subdistrict Indragiri Hilir Regency is one of the beliefs of the Banjar tribe which in the Banjar tribe means that Mandi Mayang is a purification of self to dispel bad luck. The formulation of the problem discussed in this study is economic capital in the Mandi Mayang tradition of the Banjar Community in Keritang District, Indragiri Hilir Regency and Economic Capital in the Mandi Mayang tradition of the Banjar Community in Keritang District, Indragiri Hilir Regency. The subjects of this study were 7 people whose subjects were the leader of Mandi Mayang and the person who had carried out the Mandi Mayang tradition. The informant's research technique in this study was by using a purposive sampling technique. The method used is descriptive qualitative research method. The theory used is the theory of economic capital and social capital proposed by Putnam which consists of networks, norms, and beliefs. The results of the study can be concluded that economic capital and social capital are very important in the Mandi Mayang tradition of the Banjar community. Economic capital and social capital are very prominent in the Mandi Mayang tradition of the Banjar community, namely with the presence of economic capital the Mandi Mayang tradition is still carried out because the Mandi Mayang tradition requires economic capital in preparing Mandi Mayang requirements, and social capital is also prominent in the Mandi Mayang tradition. Keywords: Tradition of Mandi Mayang Banjar and Community